AUTOMATIC WHITEBOARD CLEANER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The principal point of our task is to save time. It's exceptionally difficult to invest our energy dependably in cleaning of the white board. This project is implemented to make human work easier and can reduce the use of human power because of its potential applications. The report puts forward a kind of mechanism design scheme; this mechanism keeps the whiteboard clean. The duster which is mounted on a wooden block moves in forward and reverse direction vertically. Duster is mounted on a chain which receives power from a shaft, on which bevel gears are mounted and a hand wheel is attached with it so that effective drive is being done. This appertains to new and useful improvements and more particularly to an apparatus whereby whiteboards can be cleaned in an easy and convenient manner. The object of the present automatic whiteboard duster is to provide an attachment for whiteboards in the form of a power driven erasing apparatus which can be set in operation, thus eliminating the drudgery of manually cleaning blackboards.